The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/rec.12036
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating Seagrass by Facilitating Recruitment: Improving Chances for Success

Abstract: Attempts to arrest seagrass loss through numerous rehabilitation methods have traditionally produced inconsistent results. On Australia's southern coast, hessian bags made from biodegradable jute fibers show promise for rehabilitating Amphibolis antarctica by facilitating recruitment of seedlings in situ. Testing ways to improve the performance of bags (i.e. increasing seagrass recruitment and establishment) showed that bags with a coarse outer weave of hessian facilitated greater seedling densities (approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Restoration of this site began as a trial of new techniques to facilitate the natural recruitment of A. antarctica seedlings, with the overall intention of re-establishing an extensive continuous seagrass meadow (see Irving et al 2010;Wear et al 2010;Irving et al 2013;Tanner 2014). As a result, restoration plots are replicated temporally rather than spatially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restoration of this site began as a trial of new techniques to facilitate the natural recruitment of A. antarctica seedlings, with the overall intention of re-establishing an extensive continuous seagrass meadow (see Irving et al 2010;Wear et al 2010;Irving et al 2013;Tanner 2014). As a result, restoration plots are replicated temporally rather than spatially.…”
Section: Discussionmentioning
confidence: 99%
“…antarctica seedlings (Irving et al 2013). While not formally measured due to the small size of the entire site (~ 2 km between the edge of the seagrass and shoreline, Wear et al 2010) there were no obvious environmental gradients present.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…46 This improved water quality has been beneficial for seagrass recovery efforts. Between 1949 and 2007, this coastline experienced a net loss of 6200 hectares of seagrass 47 influencing the quality and quantity of ecosystem service delivery. Prior to 2005, local rehabilitation trials by South Australian scientists demonstrated effective methods to improve the spatial extent and health of seagrass meadows.…”
Section: South Australiamentioning
confidence: 99%
“…Most of these trials have been published separately (Seddon ; Irving et al . , ; Wear et al . ; Tanner ), but here, we set the trials within their management context and draw implications for future research and management.…”
Section: Introductionmentioning
confidence: 99%